Effects of Silicon on the Physiological Characteristics of Stress Resistance of Cryptocoryne parva Tube Seedlings - Yulu GAN; Feng FENG; Ziyun FAN; Xingxing XIANG; Yining YU; Canqiang CHEN (Guangdong nongye kexue, 2023)
【Objective】The study aims to explore the effects of silicon on the physiological characteristics of Cryptocoryne parva test-tube seedlings, and provide theoretical and technical support for increasing the survival rate of transplanting in high temperature season.【Method】The adventitious buds of C. parva were used as materials, and the single factor test method was used to explore the effects of different silicon sources (potassium silicate, sodium silicate, calcium silicate and silica) and silicon concentrations (0, 0.2, 0.4, 0.6, 0.8 and 1.0 g/L) on the proliferation coefficient, soluble sugar and soluble protein content, and antioxidant enzyme activity of C. parva test-tube seedlings, and the best silicon source and silicon concentration were selected. The selected system was used in the rooting medium of adventitious buds, and high temperature and high humidity stress were performed after transplanting, with no silicon treatment as the control, to study its effect on the stress resistance characteristics of mini C. parva.【Result】Except for the treatment with 0.6 g/L potassium silicate, there was no significant difference in proliferation coefficient of the adventitious bud of C. parva and that of CK, and the rest treatments were significantly lower than CK. The soluble sugar content of adventitious buds treated with potassium silicate and sodium silicate was significantly higher than that of CK after 25 days of culture. After treatment with 0.4 g/L sodium silicate, the soluble sugar content increased by 97.92% compared with that of CK. After adding silicon dioxide, the soluble protein content of adventitious buds treated with each concentration was significantly higher than that of CK, with an increase of 13.49%-26.63%. The addition of four silicon sources increased the POD and SOD activities of adventitious buds in different degrees. The SOD activity of adventitious buds treated with calcium silicate and silicon dioxide increased by 13.49%-62.87% and 0.86%-75.85%, respectively, compared with CK. After adding 0.2 g/L sodium silicate, the SOD activity of adventitious buds increased by 45.43% compared with CK. The MDA content of adventitious buds treated with silicon was significantly lower than that of CK, and the indexes were the best when 0.6 g/L potassium silicate was added, that is, the proliferation coefficient of adventitious buds was 2.67. In addition, compared with CK, the contents of soluble sugar and soluble protein increased by 95.39% and 27.34% respectively, the activities of POD and SOD increased by 137.67% and 39.01% respectively, and the content of MDA decreased by 56.20%. After 5 days of high temperature and high humidity stress, the soluble sugar, soluble protein, chlorophyll contents and the POD and SOD activities of adventitious buds treated with 0.6 g/L potassium silicate treatment were significantly higher than those in CK.【Conclusion】When the mini adventitious buds of C. parva treated with MS + 6-BA 4.0 mg/L + NAA 0.2 mg/L + AD 10 mg/L + potassium silicate 0.6 g/L, the contents of soluble sugar and soluble protein and the activities of POD and SOD are significantly higher than those of CK, and it is helpful to enhance the stress resistance of mini C. parva seedlings under high temperature and high humidity environment.